MANAJEMEN STRATEGI ANALISIS SWOT DALAM MENGHADAPI PERSAINGAN BISNIS PADA BMT NU PUSAT GAPURA SUMENEP - Misbahuddin (Al-Idarah, 2021)
SWOT analysis is a form of analysis within company management or within organizations that can systematically assist in the preparation of a mature plan to achieve goals, both short-term and long-term goals. This analysis must be applied by a company. The purpose and benefits of a SWOT analysis are to combine four factors or compositions accurately on how to strangth, weaknes, opportunities and threath. The SWOT analysis method can be considered as the most basic method of analysis, which is useful for looking at a topic or a problem.To facilitate understanding in this study, researchers used qualitative research methods. The data obtained by researchers in the field include interviews with leaders of BMT NU Pusat Gapura Sumenep to find out strategies to face business competition. In addition, the data collection techniques were carried out by researchers by means of interviews, observation and documentation. In this study also, the presence of researchers is very important because researchers are human instruments as well as data collectors